Cheniella tsoongii (Leguminosae: Cercidoideae), a rare, critically endangered new species from southern China - Peng, Xia; Jiang, Kai-Wen; Fang, Tian-Song; Gu, Qiao-Yun; Gu, Shi-Ran; Xie, Zhi; Duan, Lei; Li, Shi-Jin; Wang, Xiang-Ping; Shi, Miao-Miao; Tu, Tie-Yao; Zhang, Dian-Xiang (Phytotaxa, 2024)
We describe here a rare, critically endangered new species of the genus Cheniella from Guangdong province of southern China. Cheniella tsoongii is morphologically similar to C. corymbosa, and can be distinguished by having a combination of deeply-bilobed hairy leaves, white flowers, shorter hypanthia, yellow anthers, and densely ferruginous-tomentose inflorescence rachides, pedicles and hypanthia. We suggest assessing the conservation status of the species as Critically Endangered (CR) as it possesses an extremely high risk of extinction based on the rapid population declines during the last century and, only no more than 10 individuals remain in an environmentally unprotected area now. Urgent conservation studies and actions are necessary to prevent the extinction of this species.